Biblioteki, książki, ludzie. Druki z proweniencją żagańskiej biblioteki klasztornejw zbiorach Biblioteki Uniwersytetu Zielonogórskiego = Libraries, books, people. Prints with the provenance of Żagań monastery library in the collection of University Library in Zielona Góra - Nodzyńska, Ewa (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The introduction of the article provides a description of the range of special collections gathered in the University Library in Zielona Gora. The range consists of old prints, 19th-century books, primers in various languages, artistic books, old maps, bibliophile prints and valuable iconography.
Keywords: Żagań - Klasztor Augustianów - historia; Żagań - biblioteka klasztoru kanonikow regularnych św. Augustyna; zbiory specjalne; barokowe biblioteki klasztorne; starodruki; drukarstwo - 16-18 w.; Biblioteka Uniwersytetu Zielonogórskiego; Ordo Canonicorum Regularium Sancti Augustin monastery library in Żagań; baroque monastery libraries; special collections; old prints; printing of 16th-18th centuries; University Library in Zielona Gora